Edugame Pengenalan Bagian-Bagian Tubuh Manusia Dengan Tiga Bahasa Berbasis Android - Ariadi, Said, Heru Supriyono, ST. MSc. PhD (2017)
Parts of the human body is the basic thing that must be recognized by children. By getting to know the child's limbs can also find out the function of that body part. The introduction of these body parts will be easier through educational games. In addition to introduction of the body parts, in this game also gives the knowledge of three languages that is Bahasa Indonesia, English and Javanese. The purpose of making this edugame is to provide new learning to children so that can create fun and interactive atmosphere of learning and so can increase interest in learning. At the present time the majority of people have android smartphones, with it expected this edugame on android smartphone will be easy to use by children. This edugame is presented in two dimensional visual display created using Construct 2 r239. In the manufacturing process is also required CorelDraw and Photoshop to design and build assets of edugame. The method used in the manufacture process of this edugame is System Development Life Cycle (SDLC) Waterfall model approach. According to the results of tests performed in SD Muhammadiyah 16 Karangasem on students grade 4 is known by 97, 33% said edugame can help students get to know members of the body and as many as 95, 33% of students stated this edugame can increase students' interest to learn the language. From the test were obtained an average percentage of 94, 67% indicate that this edugame can create an interactive and fun learning so that attract students to study the human body parts and learn the language. Keywords: Human Body, Edugame, Android, Construct 2, SDLC